Cascaded gain-switching in the mid-infrared region. Issue 1 (December 2017) - Luo, Hongyu; Li, Jianfeng; Zhu, Chen; Lai, Xue; Hai, Yongchen; Liu, Yong
Abstract In this report, we demonstrate mid-infrared dual-waveband (i.e., 3 μm and 2 μm) pulses from a cascaded gain-switched Ho3+ -doped ZBLAN fiber laser by the use of hybrid pumping of 1150 nm CW and pulse LDs for the first time. Stable 3 μm gain-switched pulses with the maximum output power 262.14 mW and shortest pulse duration of 0.824 μs were first gained at the repetition rate of 80 kHz and wavelength of 2928.5 nm. Then stable 2 μm gain-switched pulses at 2068 nm were achieved at a switchable repetition rate between 40 kHz and 80 kHz. The maximum output power and shortest pulse duration were 75.23 mW and 0.787 μs, respectively (not simultaneously). Between them, there is a power-dependent μs-order time delay. This dual-waveband laser source has great potential in laser surgery, material processing.